2022
DOI: 10.3389/fmicb.2022.875050
|View full text |Cite
|
Sign up to set email alerts
|

Planktonic Aggregates as Hotspots for Heterotrophic Diazotrophy: The Plot Thickens

Abstract: Biological dinitrogen (N2) fixation is performed solely by specialized bacteria and archaea termed diazotrophs, introducing new reactive nitrogen into aquatic environments. Conventionally, phototrophic cyanobacteria are considered the major diazotrophs in aquatic environments. However, accumulating evidence indicates that diverse non-cyanobacterial diazotrophs (NCDs) inhabit a wide range of aquatic ecosystems, including temperate and polar latitudes, coastal environments and the deep ocean. NCDs are thus suspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 109 publications
2
25
0
Order By: Relevance
“…However, in this study, we did not detect any nif H gene OTUs related to photoautotrophs, such as cyanobacteria and the UCYN-A symbiont, as detected in other polar regions [11,97]. The high availability of organic carbon provided by eukaryotic photosynthesis and the dark chemoautotrophic activity observed in these waters of Chile Bay, which is reinforced by the possible occurrence of diazotrophic chemoautotrophs and heterotrophs, further support the cosmopolitan distribution of these organisms in the ocean [28,73,89], which now includes Western Antarctica. Chemoautotrophy, an important process for dark carbon fixation in Chile Bay, has previously been detected by active genes related to ribulose-1,5bisphosphate carboxylase/oxygenase (RuBisCO) (the Calvin cycle) [39]; however, only <5.6% of all best-hit related sequences in our phylogenetic reconstruction of the nif H gene were identified as chemoautotrophs with potential as N 2 fixers; that is, a coupling of both processes.…”
Section: Diazotrophs In Chile Baysupporting
confidence: 66%
See 3 more Smart Citations
“…However, in this study, we did not detect any nif H gene OTUs related to photoautotrophs, such as cyanobacteria and the UCYN-A symbiont, as detected in other polar regions [11,97]. The high availability of organic carbon provided by eukaryotic photosynthesis and the dark chemoautotrophic activity observed in these waters of Chile Bay, which is reinforced by the possible occurrence of diazotrophic chemoautotrophs and heterotrophs, further support the cosmopolitan distribution of these organisms in the ocean [28,73,89], which now includes Western Antarctica. Chemoautotrophy, an important process for dark carbon fixation in Chile Bay, has previously been detected by active genes related to ribulose-1,5bisphosphate carboxylase/oxygenase (RuBisCO) (the Calvin cycle) [39]; however, only <5.6% of all best-hit related sequences in our phylogenetic reconstruction of the nif H gene were identified as chemoautotrophs with potential as N 2 fixers; that is, a coupling of both processes.…”
Section: Diazotrophs In Chile Baysupporting
confidence: 66%
“…However, more effort is needed to evaluate the real effect of phosphorus and other elements, such as iron (which was not evaluated in the present study), on diazotrophic organisms, like that seen for Trichodesmium cultures from the central Atlantic Ocean [107]. In addition, to better understand the functioning of these diazotrophic heterotrophs and chemoautotrophs found here in the WAP, laboratory studies on the physiological adaptations to avoid oxygen-induced nitrogenase inhibition [108][109][110] are now necessary, as are studies on the existence of potential microenvironments in sinking particles [73,85].…”
Section: Effect Of Environmental Variables On N 2 Fixation Ratesmentioning
confidence: 78%
See 2 more Smart Citations
“…Studies have indicated that aquatic diazotrophs include autotrophic (Zehr, 2011), heterotrophic (Bombar et al, 2016; Riemann et al, 2010) and mixotrophic (Benavides et al, 2020; Feng et al, 2010) metabolism to maintain the energetic requirements of the nitrogenase enzyme. Aquatic diazotrophs can be found in benthic mats, organized in long filamentous chains (up to few hundreds of micrometers), free living planktonic cells, or associated with aggregates (Bergman et al, 2013; Bertics et al, 2010; Riemann et al, 2022).…”
Section: Introductionmentioning
confidence: 99%